DISKRIMINASI RAS DALAM NOVELA HEART OF DARKNESS KARYA JOSEPH CONRAD - NDIBA, VIRSA AMANDA PRICILLIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This skripsi which is entitled â€œDiskriminasiRasdalamNovelaHeart of DarknessKarya Joseph Conradâ€ is a study about the social life of the African people to face the racial discrimination through the story and characters in the novella. There are two questions to be answered in this research namely: How the Racial Discrimination reflected in the novella Heart of Darkness and what is the effect of racial discrimination to all the society in Africa. The aims of this research are to analyze the reflection of racial discrimination by the white people in the novel and to analyze the social effect of racial discrimination to the black people in Africa. The writer uses theory from Aristotle, Wellek and Warren, and De Bonald to describe how the racial discrimination in Africa and what the effect to the people who face discrimination. The intrinsic and extrinsic approaches are applied and the descriptive method is used in this research. The result shows that discrimination give big effect to the black people in Africa who face the savagery and the violence. Â  Keywords:Â  Racial Discrimination, Effect, Black People, Heart of Darkness